CARD8 inflammasome activation triggers pyroptosis in human T cells. (25th August 2020) - Linder, Andreas; Bauernfried, Stefan; Cheng, Yiming; Albanese, Manuel; Jung, Christophe; Keppler, Oliver T; Hornung, Veit
Abstract: Inflammasomes execute a unique type of cell death known as pyroptosis. Mostly characterized in myeloid cells, caspase‐1 activation downstream of an inflammasome sensor results in the cleavage and activation of gasdermin D (GSDMD), which then forms a lytic pore in the plasma membrane. Recently, CARD8 was identified as a novel inflammasome sensor that triggers pyroptosis in myeloid leukemia cells upon inhibition of dipeptidyl‐peptidases (DPP). Here, we show that blocking DPPs using Val‐boroPro triggers a lytic form of cell death in primary human CD4 and CD8 T cells, while other prototypical inflammasome stimuli were not active. This cell death displays morphological and biochemical hallmarks of pyroptosis. By genetically dissecting candidate components in primary T cells, we identify this response to be dependent on the CARD8‐caspase‐1‐GSDMD axis. Moreover, DPP9 constitutes the relevant DPP restraining CARD8 activation. Interestingly, this CARD8‐induced pyroptosis pathway can only be engaged in resting, but not in activated T cells. Altogether, these results broaden the relevance of inflammasome signaling and associated pyroptotic cell death to T cells, central players of the adaptive immune system. Synopsis: Inhibition of the dipeptidyl‐peptidase DPP9 by the compound Val‐boroPro induces activation of the CARD8 inflammasome in resting human T cells. Upon CARD8 activation, caspase‐1 cleaves its pore‐forming substrate GSDMD which executes pyroptosis. Dipeptidyl‐peptidase inhibition triggers pyroptosis in primary human T cells CRISPR‐Cas9 editing reveals a functional CARD8 inflammasome in human T cells A genetic drop‐out approach shows that DPP9 restrains CARD8 activation T cell receptor stimulation subverts CARD8‐triggered pyroptosis Abstract : Inflammatory cell death, best studied in myeloid immune cells, can also be triggered in T cells depending specifically on the CARD8 inflammosome/caspase‐1/gasdermin‐D axis.